Divergent effects of epidermal growth factor and calcipotriol on human rectal cell proliferation. Issue 12 (December 1994) - Thomas, M G; Brown, G R; Alison, M R; Williamson, R C
Abstract : Vitamin D may protect against colorectal cancer by reducing cell proliferation and inducing differentiation. By contrast, epidermal growth factor (EGF) stimulates cell proliferation and may encourage gastrointestinal mucosal healing. This study investigated the effect of a synthetic vitamin D analogue, calcipotriol, and EGF on human rectal epithelial cell proliferation in patients with familial adenomatous polyposis (FAP). In addition, a new technique to measure the cell cycle time is described. Sigmoidoscopic biopsy specimens were obtained from 14 patients with FAP. Tissue was established in organ culture, with or without the addition of EGF (n = 8), or calcipotriol (n = 6). Proliferation was determined using (a) metaphase arrest to measure the crypt cell production rate, (b) native mitotic index, and (c) the growth fraction using PC10 antibody. EGF receptor expression was shown using a polyclonal antibody AP12E. Calcipotriol reduced crypt cell production rate by 52% from mean (SEM) 5.29 (1.18) to 2.56 (0.80) cells/crypt/hour (p < 0.01) and EGF increased crypt cell production rate by 102% from 3.62 (0.59) to 7.33 (0.90) cells/crypt/hour (p < 0.05), and this tissue expressed the EGF receptor. The growth fraction was 48.40 (4.0)%, and the native mitotic index 1.08 (0.14)%. The cell cycle time was estimated as 94.5 hours and the time for mitosis as one hour. Thus, calcipotriol and EGF have divergent effects on human rectal mucosal proliferation.